Pain and Fatigue in Patients With Ankylosing Spondylitis Treated With Tumor Necrosis Factor Inhibitors: Multinational Real-World Findings. Issue 8 (21st December 2021) - Strand, Vibeke; Deodhar, Atul; Alten, Rieke; Sullivan, Emma; Blackburn, Stuart; Tian, Haijun; Gandhi, Kunal K.; Jugl, Steffen M.; Conaghan, Philip G.
Abstract : Supplemental digital content is available in the text. Abstract : Background/Objective: Patients with ankylosing spondylitis (AS) experience symptoms and comorbidities that impact their health-related quality of life (HRQoL) and ability to work. This real-world, global survey was conducted among AS patients receiving tumor necrosis factor inhibitors (TNFis) to evaluate both the frequency and severity of persistent symptoms, and the impact of pain and fatigue on HRQoL, employment status, and work activity. Methods: Patients with AS and their treating physicians from 13 countries across 5 continents completed questionnaires capturing demographics, patient symptoms, current disease status, HRQoL, current therapy, employment status, and Work Productivity and Activity Impairment. Results: Seven hundred five patients who had been receiving a TNFi for 3 months or more and completed both Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) pain and fatigue domains were included in the analysis; of these, 37.6% reported high BASDAI pain scores and 41.3% high BASDAI fatigue scores. Medical Outcomes Study–Short Form, 36-item version 2 domain, 5-dimensional EuroQoL Questionnaire, and 5-dimensional EuroQoL visual analog scale scores were significantly lower ( p < 0.0001), and Work Productivity and Activity Impairment scores significantly higher ( p < 0.0001), in patients with high levels of pain or fatigue than low levels. Conclusions: Globally, levels of pain and fatigue remained high in AS patients receiving TNFi treatment, which were significantly associated with reduced HRQoL and work productivity. Such persistent symptoms in usual care suggest a substantial unmet need in AS pharmacologic and nonpharmacologic therapeutic pathways.